2014
DOI: 10.1186/1471-2407-14-354
|View full text |Cite
|
Sign up to set email alerts
|

Tumors induce coordinate growth of artery, vein, and lymphatic vessel triads

Abstract: BackgroundTumors drive blood vessel growth to obtain oxygen and nutrients to support tumor expansion, and they also can induce lymphatic vessel growth to facilitate fluid drainage and metastasis. These processes have generally been studied separately, so that it is not known how peritumoral blood and lymphatic vessels grow relative to each other.MethodsThe murine B16-F10 melanoma and chemically-induced squamous cell carcinoma models were employed to analyze large red-colored vessels growing between flank tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In a recent study the large blood vessels in the vicinity of B16‐F10 melanomas were always functional; lymphatic vessels, however, were sometimes blocked. Blocked lymph drainage was readily identified upon necropsy after Evans Blue subcutaneous injection and this blockade could be confirmed by subcutaneous injection of Texas Red Dextran followed by immunostaining analysis . In light of the above discussion, it seems possible that a novel mechanism for blocked lymphatic drainage around malignant tumors awaits identification.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a recent study the large blood vessels in the vicinity of B16‐F10 melanomas were always functional; lymphatic vessels, however, were sometimes blocked. Blocked lymph drainage was readily identified upon necropsy after Evans Blue subcutaneous injection and this blockade could be confirmed by subcutaneous injection of Texas Red Dextran followed by immunostaining analysis . In light of the above discussion, it seems possible that a novel mechanism for blocked lymphatic drainage around malignant tumors awaits identification.…”
Section: Discussionmentioning
confidence: 88%
“…As demonstrated by Ruddell et al . in their murine B16‐F10 melanoma model, 4 of 12 mice showed blocked lymph drainage on the tumor‐draining side but LNs did not necessarily contain visible melanoma metastases. As the number of patients with metastatic melanoma in our human study was small and the follow‐up time limited, this facet of the study must be considered preliminary.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for this inhibition remains to be determined. Animal studies have shown that large tumors or metastases can divert or block lymph drainage 43 44 , however in this model the small foot tumors are located at some distance from the inguinal LNs. Moreover, none of the LNs contained gross metastases at this early stage, so that metastasis does not explain this shunting effect.…”
Section: Discussionmentioning
confidence: 93%
“…Unlike LYVE-1, which is down-regulated in response to inflammation [ 34 ], mCLCA1 expression on LECs is not impacted by TNF-α/IL-1β stimulation, suggesting that it is a useful marker of normal as well as inflamed LECs [ 30 ]. mCLCA1 is also expressed on collecting and initial lymphatic vessels [ 35 ] as well as on splenic red pulp stromal cells and thymic medullary stromal epithelial cells [ 12 ]. Our in vitro studies have identified a role for mCLCA1 as an interacting partner for LFA1 to mediate lymphocyte adhesion to LECs, as treatment of LECs with the 10.1.1 Ab significantly reduced lymphocyte adhesion [ 30 ].…”
Section: Introductionmentioning
confidence: 99%